Vinyl chloride resin composition

JP2025035579APending Publication Date: 2025-03-14SHIN ETSU POLYMER CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023142708
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-04
Publication Date
2025-03-14

AI Technical Summary

Benefits of technology

【0006】 本発明の塩化ビニル樹脂組成物にあっては、皮脂や汗に含まれるオレイン酸に対する耐性が高く、耐寒性にも優れる。このため、特に自動車内装部材として有用である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025035579000001
    Figure 2025035579000001
Patent Text Reader

Abstract

To provide a vinyl chloride resin composition suitable for producing a molded article having less deterioration due to sebum and sweat adhesion and excellent cold resistance.SOLUTION: There is provided a vinyl chloride resin composition which comprises a vinyl chloride-based resin, a phthalic acid-based plasticizer, and a polyester-based plasticizer, wherein the content of the phthalic acid-based plasticizer is 30 to 70 mass% with reference to the total content of the phthalic acid-based plasticizer and the polyester-based plasticizer. The phthalic acid-based plasticizer preferably is diisononyl phthalate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a vinyl chloride resin composition having improved resistance to sebum and sweat. [Background technology]

[0002] Conventionally, vinyl chloride resin compositions have been used in molded articles such as automobile parts and electronic / electrical device parts, and in covering materials for communication cables, electric wires, etc. (for example, Patent Document 1). Among these molded articles, those that are frequently touched by people may be required to have resistance to sebum and sweat. Since sebum and sweat contain free fatty acids (especially oleic acid), problems such as discoloration and deterioration may occur if the molded article is left in contact with the free fatty acids. In addition, these molded articles may also be required to have high cold resistance. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-070066 A Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention provides a vinyl chloride resin composition suitable for producing molded articles which are less susceptible to deterioration due to adhesion of sebum or sweat and have excellent cold resistance. [Means for solving the problem]

[0005] [1] A vinyl chloride resin composition comprising a vinyl chloride resin, a phthalic acid plasticizer, and a polyester plasticizer, wherein the content of the phthalic acid plasticizer is 30 to 70 mass% relative to the total content of the phthalic acid plasticizer and the polyester plasticizer. [2] The vinyl chloride resin composition according to [1], wherein the phthalic acid plasticizer is diisononyl phthalate. [3] The vinyl chloride resin composition according to [1] or [2], which has a brittle temperature of -35°C or lower, measured in accordance with JIS K 7216:1980. [4] The vinyl chloride resin composition according to any one of [1] to [3], wherein the polyester-based plasticizer has a viscosity of 1000 to 5000 mPa s at 25°C. [5] The vinyl chloride resin composition according to any one of [1] to [4], wherein in a test in which a test piece obtained by molding the vinyl chloride resin composition into a sheet shape is immersed in oleic acid at 80°C for 70 hours, the weight loss rate, expressed as the weight of the test piece after immersion relative to the weight of the test piece before immersion, is 10% by weight or less. Effect of the Invention

[0006] The vinyl chloride resin composition of the present invention has high resistance to oleic acid contained in sebum and sweat and also has excellent cold resistance, making it particularly useful as an automobile interior material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] <Vinyl chloride resin composition> A first aspect of the present invention is a vinyl chloride resin composition (hereinafter sometimes referred to as a "PVC composition") containing a vinyl chloride resin, a phthalic acid plasticizer, and a polyester plasticizer.

[0008] In this embodiment, the content of the phthalic acid plasticizer relative to the total content of the phthalic acid plasticizer and the polyester plasticizer is preferably 30 to 70 mass%, more preferably 40 to 65 mass%, and even more preferably 45 to 60 mass%. When the content of the phthalic acid plasticizer is equal to or more than the above lower limit, the cold resistance is further improved. When the content of the phthalic acid plasticizer is equal to or less than the upper limit, the oleic acid resistance is further improved.

[0009] In this embodiment, the total content of the phthalic acid plasticizer and the polyester plasticizer relative to 100 parts by mass of the vinyl chloride resin is preferably 40 to 200 parts by mass, more preferably 60 to 150 parts by mass, even more preferably 70 to 100 parts by mass, and most preferably 80 to 95 parts by mass. When the total content is at least the lower limit of the above range, the processability and flexibility of the PVC composition are further improved. When the total content is equal to or less than the upper limit of the above range, the inherent rigidity and hardness of the vinyl chloride resin can be utilized.

[0010] The PVC composition of this embodiment may contain other plasticizers in addition to the phthalic acid plasticizer and the polyester plasticizer. As the other plasticizer, for example, it is preferable to contain an epoxy plasticizer. The content of the other plasticizer is preferably 1 to 20 parts by mass, more preferably 2 to 15 parts by mass, further preferably 3 to 10 parts by mass, and most preferably 4 to 9 parts by mass, relative to 100 parts by mass of the vinyl chloride resin. Within the above preferred range, the processability and flexibility of the PVC composition can be further improved without impairing the cold resistance and oleic acid resistance exhibited by the phthalic acid plasticizer and polyester plasticizer.

[0011] Phthalic acid plasticizers are esters formed by reacting phthalic acid with a monohydric alcohol. The monohydric alcohol is preferably one having a hydroxyl group at the end of a linear or branched alkyl group having 4 to 20 carbon atoms, more preferably one having a hydroxyl group at the end of a linear alkyl group having 6 to 16 carbon atoms, even more preferably one having a hydroxyl group at the end of a linear alkyl group having 8 to 12 carbon atoms, and most preferably diisononyl phthalate (DINP).

[0012] The polyester plasticizer is a compound different from the above-mentioned phthalic acid plasticizer in that it has at least three ester bonds in the molecule. For example, it is preferable that the polyester chain formed by the reaction of a polyhydric alcohol with a dicarboxylic acid is contained in the molecule.

[0013] Examples of polyhydric alcohols include ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-hexanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, and neopentyl glycol.

[0014] Examples of dicarboxylic acids include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, phthalic acid, isophthalic acid, and terephthalic acid.

[0015] From the viewpoint of enhancing the oleic acid resistance of the PVC composition of this embodiment, an adipic acid polyester plasticizer using adipic acid is preferred.

[0016] From the viewpoint of increasing the oleic acid resistance of the PVC composition of this embodiment, the viscosity (25°C) as an index correlated with the molecular weight of the polyester-based plasticizer is preferably 1000 to 5000 mPa·s, more preferably 2000 to 4000 mPa·s, even more preferably 2500 to 3500 mPa·s, and most preferably 2800 to 3200 mPa·s.

[0017] The vinyl chloride resin may be a homopolymer of vinyl chloride (PVC) or a copolymer. Examples of copolymerizable monomers include ethylene, propylene, acrylonitrile, vinyl acetate, maleic acid or its ester, acrylic acid or its ester, methacrylic acid or its ester, vinylidene chloride, etc.

[0018] The vinyl chloride resin of this embodiment is preferably a vinyl chloride homopolymer. When it is a copolymer, the content of repeating units other than vinyl chloride is preferably 50 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 10 parts by mass or less, per 100 parts by mass of repeating units derived from vinyl chloride. The vinyl chloride resin of the present embodiment may be chlorinated after the resin is formed.

[0019] The average polymerization degree of the vinyl chloride resin of this embodiment is not particularly limited, but is, for example, preferably 1000 to 4000, more preferably 1200 to 3000, and even more preferably 1300 to 2000. When the average polymerization degree is within the above preferred range, it becomes easy to obtain a hardness suitable for automobile interior members. Here, the average degree of polymerization of the vinyl chloride resin is the average degree of polymerization measured in accordance with JIS K6720-2. The average degree of polymerization is calculated from the K value. The K value is a value measured in accordance with JIS K7367-2 (ISO1628-2).

[0020] The content of the vinyl chloride resin relative to the total mass of the PVC composition of this embodiment is preferably 25 to 53 mass%, more preferably 30 to 50 mass%, further preferably 35 to 48 mass%, and most preferably 40 to 45 mass%. When in the above preferred range, the blending ratio with other components becomes appropriate, and cold resistance and resistance to oleic acid are easily obtained.

[0021] The PVC composition of this embodiment may contain a resin other than the vinyl chloride-based resin. From the viewpoint of fully obtaining the effects of the present invention, the content of the resin other than the vinyl chloride-based resin is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, per 100 parts by mass of the vinyl chloride-based resin.

[0022] The PVC composition of this embodiment may contain any additives, such as a heat stabilizer, a processing aid (lubricant), an ultraviolet absorber, a light stabilizer, an antioxidant, a crystal nucleating agent, an antistatic agent, a metal deactivator, a filler such as calcium carbonate, an antibacterial agent, or a pigment, as long as the effects of the present invention are not impaired.

[0023] Examples of the heat stabilizer include a lead-based stabilizer, a tin-based stabilizer, a silver-based stabilizer, a calcium-magnesium-zinc-based stabilizer, a calcium-zinc-based stabilizer, a barium-zinc-based stabilizer, a barium-cadmium-based stabilizer, and a hydrotalcite-based stabilizer. One or more heat stabilizers may be included. The total content of the heat stabilizer is preferably 0.1 to 8 parts by mass, more preferably 1 to 5 parts by mass, and still more preferably 1 to 3 parts by mass with respect to 100 parts by mass of the vinyl chloride resin.

[0024] Examples of the processing aid include acrylic lubricants such as methyl acrylate and methyl methacrylate, fatty acid amide lubricants such as stearic acid amide and oleic acid amide, waxes such as paraffin wax, polyolefin wax, ester wax, montanic acid wax, and polyethylene wax, higher fatty acids such as stearic acid and behenic acid, higher alcohols such as stearyl alcohol and cetyl alcohol, fatty acid esters such as butyl stearate and monoglyceride stearate, metal soaps such as calcium stearate and magnesium stearate, and oils such as silicone oil and process oil. One or more processing aids may be included. The total content of the processing aid is preferably 0.1 to 8 parts by mass, more preferably 1 to 5 parts by mass, and still more preferably 1 to 3 parts by mass with respect to 100 parts by mass of the vinyl chloride resin.

[0025] <Method for producing PVC composition> The method for producing the PVC composition of this embodiment is not particularly limited, and it can be obtained by mixing and kneading by a conventional method so that each component becomes uniform in the composition. Examples of the method for mixing and kneading the vinyl chloride resin, each plasticizer, and other auxiliaries include methods using a pressure kneader, a Banbury mixer, etc. From the viewpoint of preventing the decomposition of PVC during mixing, it is preferable to mix and knead at a resin temperature of 180°C or lower.

[0026] <Form of PVC composition> Specific forms of the PVC composition of this embodiment may be pellets, beads, powders that are easily subjected to another molding process, or molded articles molded by known molding methods such as press molding, injection molding, and extrusion molding. The molded article is not particularly limited, and examples thereof include automobile interior members, electronic and electrical equipment parts such as personal computers and copiers, and coating materials for electric wires and cables. Since the PVC composition of this embodiment is excellent in cold resistance and oleic acid resistance, it is particularly useful as an automobile interior member.

[0027] <Physical properties of the PVC composition> (Cold resistance; embrittlement temperature) Using the PVC composition of this aspect, an A-shaped test piece defined by JIS K 7216:1980 (Test method for embrittlement temperature of plastics) is produced, and the embrittlement temperature is measured according to the same standard, whereby the cold resistance of the PVC composition of this aspect can be evaluated. The lower the embrittlement temperature of the PVC composition of this aspect, the more preferable it is, preferably -35°C or lower, and more preferably -40°C or lower.

[0028] (Oleic acid resistance) Using the PVC composition of this aspect, a sheet-like test piece is produced and immersed in heated oleic acid (for example, 80°C) for a predetermined period (for example, 70 hours), and the weight loss rate of the test piece is calculated from the following formula, whereby the oleic acid resistance of the PVC composition of this aspect can be evaluated. Formula: {(weight before immersion) - (weight after immersion)} ÷ (weight before immersion) × 100% The lower the above weight loss rate of the PVC composition of this aspect, the more preferable it is, preferably 10% or less, and more preferably 8% or less.

Examples

[0029] Hereinafter, the present invention will be specifically described with reference to examples, but the present invention is not limited only to these examples.

[0030] The details of the raw materials described in Table 1 are as follows. "PVC with a degree of polymerization of 1300" is GR-1300S manufactured by Shin-Etsu Chemical Co., Ltd. "Phthalic acid-based plasticizer" is DINP manufactured by J-PLUS Co., Ltd., which is diisononyl phthalate. The "polyester plasticizer" is ADEKA's PN-1030, a plasticizer with polyester chains formed by the polymerization of adipic acid and polyhydric alcohol in the molecule. It has a viscosity of 3000 mPa·s at 25°C and a freezing point of -25°C. "Epoxidized soybean oil" is Chemicizer SE-100 manufactured by Sanwa Synthetic Chemical Industry Co., Ltd., an epoxy-based plasticizer having a triglyceride structure. "Ba-Zn stabilizer 1" is Adeka STAB AC-299 manufactured by ADEKA Corporation, and is a general-purpose heat stabilizer. "Ba-Zn stabilizer 2" is Adeka STAB AP-550 manufactured by ADEKA Corporation, and is a general-purpose heat stabilizer. The "benzotriazole-based ultraviolet absorber" is KEMISORB 79 manufactured by ADEKA Corporation, which is a general-purpose ultraviolet absorber. The "acrylic processing aid" is Mitsubishi Chemical's Metablen P-530A, whose long molecular chains become entangled with the PVC molecules of the matrix resin, creating a pseudo-crosslinked state and imparting melt elasticity. "Calcium carbonate" is Whiten-SB manufactured by Shiraishi Calcium Co., Ltd., a general-purpose filler. "Methylphenylpolysiloxane" is KF-54 manufactured by Shin-Etsu Chemical Co., Ltd. and is a type of silicone oil. "Pigment" is Resinocolor Black HE-451-C, a black pigment.

[0031] <Preparation of Composition> The raw materials were mixed in the amounts (parts by mass) shown in Table 1 using a twin-screw kneader to obtain a PVC composition. For example, in Example 1, 60 parts by mass of phthalic acid plasticizer, 30 parts by mass of polyester plasticizer, 5 parts by mass of epoxidized soybean oil, and 30.9 parts by mass of other auxiliary agents (stabilizers 1 and 2, UV absorber, acrylic processing aid, calcium carbonate, silicone oil, pigment) were blended with 100 parts by mass of PVC to obtain the target PVC composition, totaling 225.9 parts by mass.

[0032] <Creating a sheet> 100 g of the PVC composition of each test example was kneaded for 10 minutes with a 3.5-inch roll set at 155 ° C to prepare a sheet with a thickness of 0.5 mm. The sheet prepared here can be distinguished between the direction in which it passed through the roll (flow direction) and the direction perpendicular thereto. A plurality of sheets were prepared, stacked with the flow directions of directly contacting sheets crossing each other, preheated at 170 ° C for 4 minutes, and then heat-compressed and molded at 170 ° C and 15 MPa for 4 minutes, and then slowly cooled to room temperature (25 ° C) while still under pressure to obtain a sheet of a predetermined thickness specified for each test, which was then used for tests of cold resistance and oleic acid resistance.

[0033] <Cold resistance; embrittlement temperature> In accordance with JIS K 7216:1980 (Test method for brittle temperature of plastics), the brittle temperature was determined using A-type test pieces specified in the same standard.

[0034] <Oleic acid resistance> The test piece used was a sheet-like test piece with a length and width of 30 mm x width of 120 mm and a thickness of 2 mm, prepared by the method described above. The weight of the test piece was measured in advance, and it was immersed in oleic acid in a container and kept in a thermostatic chamber at 80°C for 70 hours. After that, it was removed from the container, the oleic acid was wiped off, and the weight of the test piece was measured again, and the weight loss rate before and after immersion was calculated using the following formula. Formula: {(weight before immersion) - (weight after immersion)} ÷ (weight before immersion) x 100%

[0035] It is known that human sebum and sweat contain large amounts of oleic acid, and low solubility in oleic acid (low weight loss rate) indicates that the test piece has excellent resistance to oleic acid, meaning that the test piece is less susceptible to discoloration and deterioration after sebum or sweat adheres to it.

[0036] [Table 1]

[0037] In the PVC composition of Example 1, the content of the phthalic acid plasticizer relative to the total of the phthalic acid plasticizer and the polyester plasticizer was 67%, and the solubility in oleic acid was sufficiently suppressed compared to Comparative Example 1. In addition, the brittleness temperature was sufficiently low, and the cold resistance was also excellent. In the PVC composition of Example 2, the content of the phthalic acid plasticizer relative to the total of the phthalic acid plasticizer and the polyester plasticizer was 50%, and the solubility in oleic acid was suppressed more than in Example 1. In addition, the brittleness temperature was sufficiently low and the cold resistance was also excellent. In the PVC composition of Example 3, the content of the phthalic acid plasticizer relative to the total of the phthalic acid plasticizer and the polyester plasticizer was 33%, and the solubility in oleic acid was further suppressed compared to Examples 1 and 2. In addition, the brittle temperature was lower than that of Comparative Example 2, and the cold resistance was also good.

[0038] The PVC composition of Comparative Example 1 does not contain a polyester-based plasticizer, and therefore, although the total plasticizer content is the same as in Examples 1 to 3, it has high solubility in oleic acid and it is clear that discoloration and deterioration after sebum or sweat adheres to the test specimen cannot be suppressed. The PVC composition of Comparative Example 2 does not contain a phthalic acid plasticizer, and therefore, although the total plasticizer content is the same as in Examples 1 to 3, it clearly has a high brittle temperature and poor cold resistance.

Claims

1. A vinyl chloride resin composition comprising a vinyl chloride resin, a phthalic acid plasticizer, and a polyester plasticizer, The vinyl chloride resin composition, wherein a content of the phthalic acid-based plasticizer is 30 to 70 mass% based on a total content of the phthalic acid-based plasticizer and the polyester-based plasticizer.

2. 2. The vinyl chloride resin composition according to claim 1, wherein the phthalic acid plasticizer is diisononyl phthalate.

3. 3. The vinyl chloride resin composition according to claim 2, having a brittle temperature of −35° C. or lower, measured in accordance with JIS K 7216:1980.

4. 4. The vinyl chloride resin composition according to claim 3, wherein the polyester plasticizer has a viscosity of 1000 to 5000 mPa·s at 25°C.

5. 5. The vinyl chloride resin composition according to claim 4, wherein in a test in which a test piece obtained by molding the vinyl chloride resin composition into a sheet is immersed in oleic acid at 80° C. for 70 hours, a weight loss rate, expressed as the weight of the test piece after immersion relative to the weight of the test piece before immersion, is 10% by weight or less.

Citation Information

Patent Citations

  • Oil-resistant material

    JP1995188492A

  • Vinyl chloride resin composition

    JP1996165393A

  • Flexible conduit using vinyl chloride resin composition

    JP2001050442A

  • Vinyl chloride-based resin composition

    JP2010168409A

  • Phthalic acid ester composition

    WO2021002406A1